2014
DOI: 10.1103/physrevd.90.126006
|View full text |Cite
|
Sign up to set email alerts
|

Holographicp-wave superfluid

Abstract: In the probe limit, we numerically construct a holographic p-wave superfluid model in the four-dimensional (4D) and five-dimensional (5D) anti-de Sitter black holes coupled to a Maxwellcomplex vector field. We find that, for the condensate with the fixed superfluid velocity, the results are similar to the s-wave cases in both 4D and 5D spacetimes. In particular, the Cave of Winds and the phase transition always being of second order take place in the 5D case. Moreover, we find the translating superfluid veloci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…4(b), the evident first-order transition emerges for z = 1, which agrees with the result in Ref. [50]. However, with the increasing z, the character of the first-order transition (such as the double value of the condensate curve) becomes less obvious until the appearance of the second-order transition in the cases of z = 7 5 and 3 2 , which not only means that the improving z hinders the emergence of the first-order phase transition, but also agrees with the phase diagram in Fig.…”
Section: Condensates Versus the Temperaturesupporting
confidence: 90%
See 3 more Smart Citations
“…4(b), the evident first-order transition emerges for z = 1, which agrees with the result in Ref. [50]. However, with the increasing z, the character of the first-order transition (such as the double value of the condensate curve) becomes less obvious until the appearance of the second-order transition in the cases of z = 7 5 and 3 2 , which not only means that the improving z hinders the emergence of the first-order phase transition, but also agrees with the phase diagram in Fig.…”
Section: Condensates Versus the Temperaturesupporting
confidence: 90%
“…[2], a new holographic p-wave superconductor model was built by coupling a Maxwell-complex vector (MCV) field with the four-dimensional (4D) Schwarzschild AdS black hole [43], for related works, see Refs. [44][45][46][47][48][49][50]. It was shown that only the external magnetic field can induce the condensate, which is similar to result of the QCD vacuum phase transition in Ref.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…The results in this paper can also be get form the extension of the complex vector holographic p-wave model [41,42] as given in ref. [17].…”
Section: The Model Setupmentioning
confidence: 91%